Giving Up the Chair Role and Rejoining the Faculty - Stephen F Pyle; David A Line (Academic Chairpersons Conference Proceedings, 2023)
Chairpersons often return to faculty with little planning or preparation. For many, this transition can lead to role confusion, performance issues, loss of relationships and feelings of inadequacy. This interactive presentation, informed by research, will equip chairs and administrators with critical planning components in support of successful return to faculty.
Keywords: Chairperson; Career Transition; Return to Faculty; Transition Planning